5-Aza-2′-deoxycytidine induces human Tenon's capsule fibroblasts differentiation and fibrosis by up-regulating TGF-β type I receptor. (December 2017) - Fu, Shuhao; Sun, Li; Zhang, Xiaoyan; Shi, Huimin; Xu, Kang; Xiao, Yiqin; Ye, Wen
Abstract: The principle reason of high failure rate of glaucoma filtration surgery is the loss of filtration function caused by postoperative scar formation. We investigated the effects of 5-aza-2′-deoxycytidine (5-Aza-dc), a DNA methyltransferases inhibitor, on human Tenon's capsule fibroblasts (HTFs) differentiation and fibrosis and its mechanism of action, especially in relation to transforming growth factor (TGF)-β1 signaling. TGF-β1 was used to induce differentiation of cultured HTFs. 5-Aza-dc suppressed DNA methyltransferases (DNMTs) activity 6 h after treatment with a course corresponding to that of TGF-β1-induced reduction of DNMT activity without affecting cell viability as measured by Cell Counting Kit-8 assay. 5-Aza-dc also reduced DNMT1 and DNMT3a protein expression from 24 to 48 h. HTFs migration evaluated by scratch-wound assay were significantly increased 24 h after 5-Aza-dc treatment, a time course similar to that of TGF-β1. Treatment with 5-Aza-dc significantly increased the mRNA and protein levels of α-smooth muscle actin (α-SMA), collagen-1A1 (Col1A1), fibronectin (FN) and TGF-β type I receptor (TGFβRI). Furthermore, the effects of 5-Aza-dc on DNMT activity suppression, cell migration, and fibrosis were all reversed by a TGFβRI inhibitor- SB-431542. Meanwhile, knockdown of DNMT1 upregulated TGFβRI expression and had the same fibrosis-inducing effect in HTFs, which was also inhibited by SB-431542. Thus, the results indicate that DNA hypomethylation induces HTFs differentiation and fibrosis through up-regulation of TGFβRI. DNA methylation status plays an important role in subconjunctival wound healing. Highlights: Effect of 5-Aza-2′-deoxycytidine on fibrosis-related genes expression in Human Tenon's Capsule Fibroblasts is provided. The mechanism relies on up-regulation of TGFβRI. Establish the role of DNA methylation during subconjunctival fibrosis.